TRADISI ILMIAH DALAM PENDIDIKAN PESANTREN - Ainul Yaqin; Nanda Septiana (JIE (Journal of Islamic Education), 2019)
This study describes the education that developed in Islamic boarding schools. The focus of the discussion is the existence and traditions that exist in the pesantren. The writing method used to obtain data is the library method. The conclusions obtained in this paper are Islamic boarding schools are a real form of educational manifestations that are able to form a strong personality for each of their students. Islamic boarding schools are an original form of archipelago education created with Islamic tradition values ​​that have their own uniqueness in building civilization. The form of scientific tradition that was built in pesantren in the form of education in the form of munadharah, a pattern of education maintained and maintained with its classical form in pesantren, collecting books and classical manuscripts to establish libraries containing various sciences and integrated in santri as human beings who love science. With the tradition that is owned, Islamic boarding schools are able to build the character of the santri to become human beings who are able to maintain scientific traditions that have long been built by 'ulama' for the sake of science and future sustainability.